2011
DOI: 10.1002/ibd.21617
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in statural growth impairment in Crohnʼs disease: Role of IGF-1

Abstract: Background-Growth impairment in Crohn's disease (CD) is more common in males than females for unknown reasons. Since insulin-like growth factor 1 (IGF-1) is required for statural growth, we hypothesized that IGF-1 levels are lower in males with CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 42 publications
3
48
1
Order By: Relevance
“…However, during states of pure malnutrition (such as in anorexia nervosa), IGF-1 levels are low, demonstrating GH resistance [25], [26]. Although IGF-1 is commonly seen as a marker of nutritional status, IGFBP-3 is more stable in states of under nutrition and is more commonly seen as an indicator of adequate GH signaling [27]. That hsCRP was associated with higher GH levels and lower levels of IGF-1 and IGFBP-3 (suggesting lower hepatic response to GH) suggests against poor nutrition as the only reason for these associations, particularly given the lower levels of IGFBP-3 [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, during states of pure malnutrition (such as in anorexia nervosa), IGF-1 levels are low, demonstrating GH resistance [25], [26]. Although IGF-1 is commonly seen as a marker of nutritional status, IGFBP-3 is more stable in states of under nutrition and is more commonly seen as an indicator of adequate GH signaling [27]. That hsCRP was associated with higher GH levels and lower levels of IGF-1 and IGFBP-3 (suggesting lower hepatic response to GH) suggests against poor nutrition as the only reason for these associations, particularly given the lower levels of IGFBP-3 [27].…”
Section: Discussionmentioning
confidence: 99%
“…At the initial withdrawl, males and females showed a similar degree of seizure behavior, however, on subsequent withdrawal bouts, males had robust increases in seizure severity while females did not. Interestingly, this was not associated with estrogen levels or with sex differences in blood alcohol levels Veatch et al, 2007), although sex differences in blood IGF-1 levels have been reported (Chaler et al, 2009; Gupta et al, 2011). …”
Section: Introductionmentioning
confidence: 87%
“…This suggested influences beyond the delivery of calories alone. Growth deficits not explained by nutrition alone have been proposed to result predominantly from inflammation [19, 20, 21, 22, 23, 24] or from suppression of growth factors in the setting of inflammation [25, 26]. …”
Section: Discussionmentioning
confidence: 99%